Partisipasi Masyarakat dalam Pelaksanaan Program Nasional Pemberdayaan Masyarakat Mandiri Perkotaan (PNPM-MP) di Desa Bligo Kabupaten SidoarjoCommunity Participation in the Implementation of the National Urban Independent Community Empowerment Program (PN - Rahayu Kristiniati; Ilmi Usrotin Choiriyah (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2014)
The purpose of this study was describe the community participation in the implementation of the National Community Empowerment Program for Urban(PNPM-MP) in the Bligo village, Candi sub-district, Sidoarjo Regency as well as to describe the supporting factors and inhibiting factors. The method of this research used qualitative description. The results of this research show that community participation in this program implementation has been running well. It is caused at the participation stages that is consisting of monitoring and evaluation stage, the maintenance stage, and utilization of the building has been running well. However, at the decision-making stage and the implementation stage must be improved. The successful of this program implementation is influenced by supporting factors and inhibiting factors. The supporting factor is commitment of head village, participation of non-governmental organization, commitment and support of interest groups. Meanwhile, inhibiting factors are less of supervisor participates in the manager finance unit. So there are two of nongovernmental organizations that delay to refunds and community participation that is not involved in the whole of each activity.